The Newcomer’s Guide to Edmonton and Community Translation: Materially and Culturally Situated Practices - Cisneros, Odile; De Léon, Ann (TTR)

(untitled) (Association canadienne de traductologie, 2020)
In line with the current turn towards the study of material culture in Translation Studies, this paper explores community translation in Edmonton through the case study of the Newcomer’s Guide to Edmonton (NGE). A 63-page handbook of essential information for new residents published by the City of Edmonton (2016), the NGE was translated into 7 languages in a project that employed community translators. This research examines community translation as both a materially and a culturally situated practice. We discuss how the materialities of communication and translation (Littau, 2016) can be addressed through this case study on community translation (Taibi and Ozolins, 2016). We also look at the process of community translation, specifically, the material conditions under which community translators work, often as volunteers with limited training who serve newcomers. We explore the case of the translation of the NGE as a culturally situated practice where community translators faced the particularities not only of the material translated, but also of the local context and target communities. Our research suggests that the process of the NGE’s translation not only empowered translators to make appropriate choices for their local communities, but also developed strategies for elevating the quality of the final product.